ORNITHOBACTERIOSIS: A PROBLEM IN THE POULTRY INDUSTRY? - Kiyamova, Z.N. (Research Focus International Scientific Journal, 2026)
This article examines the topic “Uo‘K: 619.616.989.2.75 Ornitobakterioz – Parrandachilik Sanoatida Muammomi?” from a scientific and methodological perspective. The theoretical foundations, practical significance and relevant aspects of the study are analysed.